Maternal immunization with RSV fusion glycoprotein vaccine and substantial protection of neonatal baboons against respiratory syncytial virus pulmonary challenge. Issue 5 (29th January 2020) - Welliver, Robert C.; Papin, James F.; Preno, Alisha; Ivanov, Vadim; Tian, Jing-Hui; Lu, Hanxin; Guebre-Xabier, Mimi; Flyer, David; Massare, Michael J.; Glenn, Greg; Ellingsworth, Larry; Smith, Gale
Highlights: Recombinant RSV fusion nanoparticle vaccine is in phase 3 clinical development for maternal immunization. RSV vaccine is highly immunogenic in healthy adults and pregnant baboons. Maternal antibodies persisted in infant serum for 50 days with 14–24-day half-life. Maternal immunization substantially protects infant baboons against pulmonary RSV challenge. Abstract: Globally, human respiratory syncytial virus (RSV) is a major cause of severe lower respiratory infection in infants and young children. There are no licensed vaccines despite the high worldwide disease burden. RSV fusion (F) glycoprotein vaccine is the most advanced candidate for maternal immunization. In this report, a baboon maternal immunization model was used to assess the immunogenicity and protection of infants against pulmonary challenge with human RSV/A. Vaccination in the third trimester produced high anti-RSV F IgG titers and virus-neutralizing antibodies. Infants born to immunized females had high levels of serum RSV antibodies that were comparable to maternal levels at birth and persisted for over 50 days with a half-life of 14–24 days. Furthermore, infants from immunized females and challenged with RSV/A were healthy, developed less severe disease, and had only mild pulmonary inflammatory changes whereas infants born to non-vaccinated females developed more severe disease with marked to moderate interstitial pneumonia, pulmonary edema, and bronchiolar obstruction. These results support the further development of the RSV F vaccine for maternal immunization.